Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae) - Gill, Anthony C.; Allen, Gerald R. (Zootaxa, 2004)
Pseudochromis lugubris is described from seven specimens, 38.4 65.9 mm SL, from southeastern New Guinea. It is distinguished from congeners in having the following combination of characters: dorsal-fin rays III,26 27; anal-fin rays III,14; scales in lateral series 48 50; circumpeduncular scales 20; and caudal fin truncate to emarginate, sometimes weakly trifurcate. Pseudochromis tonozukai is described from two specimens, 62.6 65.9 mm SL, from Weh Island, northern Sumatra, Indonesia. It is distinguished from congeners in having the following combination of characters: dorsal-fin rays III,25; anal-fin rays III,14 15; scales in lateral series 34 36; caudal fin rhomboid to trifurcate; and upper part of pectoral fin without small dark spot.